Brain Abnormalities on MRI in Partial Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The incidence of cerebral abnormalities using MRI in 30 consecutive children, aged 0.9-15.5 years, presenting with intractable complex partial seizures is reported from the Institute of Child Health and Hospital for Sick Children, London, UK.